2014
DOI: 10.1109/tap.2014.2364811
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis for Active Matched Antennas With Non-Foster Elements

Abstract: Abstract-During the last years many researchers have been working on the active matching or on non-Foster matching networks for one-and two-port electrically small antennas (ESAs). A new parameter on the sensitivity of the two-port electrically small antenna when loaded with a non-Foster network is presented. This sensitivity analysis will allow us to choose what kind of antennas can be properly matched with non-Foster networks and their position in order to optimize the performance of the design. Then, a typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Two-element array loaded with a non-Foster network A multiport antenna approach is used to deduce the analytical impedance, Z^,, that have to be implemented well with an ideal non-Foster MN well with a transistorized circuit for broadband impedance matching. As a previous work in [7], the authors found the most suitable location for an active MN in a single semiloop. Such location is the opposite side from the input port.…”
Section: Active Impedance Matching Designmentioning
confidence: 66%
“…Two-element array loaded with a non-Foster network A multiport antenna approach is used to deduce the analytical impedance, Z^,, that have to be implemented well with an ideal non-Foster MN well with a transistorized circuit for broadband impedance matching. As a previous work in [7], the authors found the most suitable location for an active MN in a single semiloop. Such location is the opposite side from the input port.…”
Section: Active Impedance Matching Designmentioning
confidence: 66%
“…The active matching antenna method, proposed in [29], can be applied in this case, to calculate an analytical impedance (Z MN ) to b) The S 11 parameter at the input port for both cases: the unloaded and the active loaded monopole with the MOSFET-based NIC.…”
Section: Design Examplementioning
confidence: 99%
“…Earlier researchers mainly concentrated studies on the high frequency (HF) band [6][7][8][9][10]. Different NFCs, including CMOS based NFC [11], diode based NFC [12], and amplifier based NFC [13] have been matched to various types of antennas, including the monopole antenna [14], loop antenna [15], Egyptian axe dipole antenna [16], microstrip leaky-wave antenna [17], and parasitic array [18], with mostly favorable results.…”
Section: Introductionmentioning
confidence: 99%